Basic and reactive dye removal using natural and modified zeolites - Karadag, Dogan; Akgul, Eda; Tok, Sema; Erturk, Ferruh; Kaya, Mehmet Arif; Turan, Mustafa (AMER CHEMICAL SOC, 2007)
The adsorption of the dyes Basic Red 46 (BR46) and Reactive Yellow 176 (RY176) from aqueous solution onto natural and modified zeolites has been investigated. The surfactants cetyltrimethylammonium bromide (CTAB) and hexadecyltrimethylammonium bromide (HDTMA) were used to modify the zeolite surface, and Fourier transform infrared spectroscopy (FTIR) spectral analysis was used to confirm the surface modification. The effects of initial dye concentration, contact time, pH, temperature, ionic strength, and surfactant type on adsorption were studied in a batch system. BR46 adsorption onto natural zeolite increased to minor a extent with increasing pH, whereas pH did not significantly affect RY176 adsorption. Adsorption capacities of dyes increased with contact time, initial concentration, and temperature for both BR46 and RY176. The increase in ionic strength caused a decrease in adsorption of BR46 and an increase in adsorption of RY176. Adsorption of BR46 on natural zeolite is more favorable than RY176 on the CTAB and HDTMA modified zeolites. The adsorption of basic and reactive dyes was spontaneous and endothermic as concluded from thermodynamic assays.
Keywords: AQUEOUS-SOLUTION; ANIONIC DYE; FLY-ASH; ACTIVATED CARBON; ADSORPTION; SURFACTANT; CLINOPTILOLITE; EQUILIBRIUM; SEPIOLITE; KINETICS; Thermodynamics; Chemistry; Engineering